Fixed income relative value analysis: A practitioner`s guide to the theory, tools and trades - Huggins, Doug; Schaller, Christian (Hobeken John Wiley & Sons Inc., 2024)
Since its first edition in 2013, Fixed Income Relative Value Analysis: A Practitioner$1 (Bs Guide to the Theory, Tools, and Trades has become the gold standard for guides linking financial theories with practical analysis tools. The newly revised second edition reflects both the progress in statistical tools over the last decade and the impact of the transition to SOFR on swap spreads. You$1 (Bll find a set of statistical and financial tools, a multitude of actual trades resulting from the application of these tools, as well as access to a companion website featuring spreadsheets illustrating some of the models contained in the book.s